Alternative Economies and Spaces New Perspectives for a Sustainable Economy - Zademach, Hans-Martin; Hillebrand, Sebastian (Global Studies, 2013)
The volume entails a collection of contributions by leading scholars (Raymond Bryant, Michael K. Goodman, Benjamin Huybrechts, Andrew E.G. Jonas, Roger Lee, Peter North, and Katinka Weber) concerned with alternative modes of economic and social exchange. The cases addressed in these contributions - including credit unions, alternative currencies, sustainable consumption, and social enterprises - deliver valuable insights into how such alternatives are performed at various scales and spaces in relation to and beyond the economic mainstream. In sum, the collection provides vital grounds for both a transition of the economic system towards a more sustainable one, and a reconceptualisation of the economic itself in our scholarly thinking and everyday lives.